INFLUENCE OF ANNEALING TEMPERATURE ON ZINC OXYSULPHIDE THIN FILMS PROPERTIES DEPOSITED BY THERMAL SPRAY TECHNIQUE - Khalil , Mohammed H.; Mohammed, Raghad Y.; Ibrahem , Mohammed A. (Science Journal of University of Zakho, 2023)
This article studies the effects of annealing temperatures on the stoichiometry, structure, and optical characteristics of Zinc Oxysulphide thin films deposited on glass substrates using the thermal spray method. The annealing was done in the air under a temperature of 150 ºC, 250 ºC and 350 ºC. Field Emission Scanning Electron Microscopy (FESEM), X-ray diffractometry (XRD), and a UV-Vis Spectrophotometer were utilized to examine the thin films’ morphological, structure, and optical characteristics as grown and annealed samples. It has been observed that the film thickness decreases as the annealing temperature increases. The XRD pattern demonstrates that as-prepared and annealed samples at 250C, and 350C are amorphous, while film annealed at 150 C is crystalline with the hexagonal phase and orientated along (110) plane. FESEM image of the as-prepared Zinc Oxysulphide thin films shows flower-like sheet nanostructures. However, for the annealed samples, the FESEM images show cone-like with a combination of sheets and aggregate nanoparticles. EDX analysis reveals the presence of Zn, O as well as sulfur. The transmittance of the film decreases from 63% to 37% and the band gap energy reduces slightly from 3.99 to 3.92 eV as the annealing temperature increase.